(untitled) (MAUSAM, 2022)
During the southwest monsoon of 1976 wind velocities were measured near the vicinity of the ground using an Instrumented gust sphere. Certain definite trends were observed in the amplitude, duration and frequency of the gusts. An order of magnitude on the period of the gusts suggested that the gusts have the same characteristic of the eruptions observed in turbulent boundary layer flows.